Faktor yang Berhubungan dengan Pemberian ASI Eksklusif pada Ibu Bekerja di PMB Bidan P Kabupaten Bandung Barat - Sri Hennyati; Maya Indriati; Ade Irma Sri Ayu Lestari (Jurnal Sehat Masada, 2024)
Breast milk (ASI) is a staple food that has optimal nutrition for babies. Low intake of exclusive breast milk is a threat to children's health and development. Breastfeeding is the right of every mother, including working mothers. Working mothers are still considered to be one of the factors causing the high failure rate of exclusive breastfeeding and is a factor that hinders the success of exclusive breastfeeding. Because working mothers experience difficulties if they have to work while providing exclusive breast milk. This study aims to determine the factors associated with exclusive breastfeeding for working mothers in PMB Midwives, West Bandung Regency. The research used is correlation research. The population of this study was working mothers who had babies aged 0-12 months, and the sample was 54 people using total sampling. Instrument research used a questionnaire. bivariate analysis used Spearman's rank with a significance level of á¼€<0.05. The research results show that the knowledge variabel (p = 0.000 and a correlation value coefficient of 0.533), education (p = 0.003 and a correlation value coefficient of 0.397), attitude (p = 0.002 and a correlation value coefficient of 0.418), family support (p = 0.005 and a correlation value coefficient of correlation 0.377), availability of breastfeeding facilities (p=0.022 and correlation coefficient value 0.312). For health workers, especially midwives, it is hoped that they will further increase the provision of information and counseling to working mothers, how to express breast milk and store expressed breast milk by using various interesting supporting media, either through mass media or the internet.